Efek Ekstrak Etanol Daun Kelor (Moringa oleifera, Lamk.) Pada Mencit Model Demensia: Kajian Memori Spasial, Kadar Malondialdehid Dan Jumlah Sel Piramidal Hipokampus Area CA1 Dan CA2-CA3 - arikha ayu susilowati; Gunawan Pamudji Widodo; Jason Merari (Fakultas Farmasi Universitas Setia Budi, 2019)
ABSTRACT Dementia is a disease of nerve cells in the brain, due to the hippocampus damaged by free radicals. EEDK (Ethanol extract of kelor leaves)(Moringa oleifera, Lamk.) contains phytochemicals, carotene, vitamins, minerals, amino acids, flavonoids and phenolics, proven to reduce oxidative damage and memory deficits. This study aims to determine the effect of EEDK on spatial memory, MDA levels, the number of hippocampal pyramidal cells damaged in the CA1, CA2-CA3 area and histopathological features of mice. The design of this study was pre-test and post-test control group design for spatial memory test and post test control group design for MDA levels, hippocampal pyramidal cell counts and histopathological features. This Reseach using 30 mice divided into of 6 groups, each group consist of 5 mice, namely the normal control group, positive control, negative control, EEDK group 100, 200, and 400 mg/kg body weight, all groups induced by Pb acetate 50 mg / KgBB except the normal group. Positive control was treated with quercetin 50 mg/kgBB, while negative controls were not treated. Memory test data obtained from the Morris water maze pre and post-test, antioxidant status data obtained from MDA levels and histopathological data obtained from the calculation of pyramidal cell counts. Data analysis used repeated measures ANOVA and ANOVA with Post Hoc LSD. The results showed that latency time, MDA level test and brain histopathology examination had significant differences between the negative control group and the EEDK group. EEDK 400 mg/kgBB was most effective in improving spatial memory, decreasing MDA levels, and preventing damage to the hippocampal pyramidal cell CA1, CA2-CA3 area.